(untitled) (Dermatology Reports, 2023)
Post-vaccinal and parainfectious activation of the immunity with subsequent development of a certain immunological/skinimmunological disease is not rare in clinical practice. This concept is mentioned in relation to molecular/antigenic mimicry. To this day, the pathogenesis of sarcoidosis and sarcoid-type reactions remains a mystery. Moreover, they can be a warning sign of changes in tissue homeostasis, whether they are infectious, noninfectious- immunological, tumor-related, etc. We present a rare form of erythrodermic sarcoidosis with massive systemic involvement (pericarditis, supraventricular tachycardia, hepatitis, iritis/iridocyclitis, pulmonary fibrosis/bihilar lymphadenopathy, and arthritis) developed after receiving the ChadOx1-S vaccine for COVID- 19. Systemic immunosuppressive therapy with Methylprednisolone was introduced according to a scheme (in a reduction mode with an initial dose of 40 mg/day intravenously) in combination with topical Pimecrolimus 1% cream twice a day. Rapid improvement of the symptoms was observed within the first two days of treatment. According to the scientific literature, the presented patient turns out to be the first case of erythrodermic sarcoidosis (with systemic involvement), described as a side effect after vaccination and/or administration of a certain medicinal form.